"The Master's Tools Will Never Dismantle the Master's House": Ten Critical Lessons for Black and Other Health Equity Researchers of Color. (June 2021) - Bowleg, Lisa
Audre Lorde's provocative admonishment, "The master's tools will never dismantle the master's house, " is a fitting caution for Black and other scholars of color who seek to use traditional social and behavioral sciences research as a tool to achieve social justice and health equity in Black communities. Invoking Lorde, I use the "master's tools" as a metaphor for conventional theoretical and methodological approaches and "dismantle the master's house" as a metaphor for intersectional structures and systems of oppression that created and sustain health inequity in U.S. Black communities. Using a blend of personal narrative and insights from a 23-year career as a Black critical health equity researcher, I share 10 critical lessons for Black and other health equity researchers of color. And because the personal typically reflects the structural, I recommend system and structural-level mitigation strategies for departments, universities, extramural institutions (e.g., journals), and the government, for each critical lesson.